Can Education Unlock Scale? The Demand Impact of Educational Games on a Large-Scale Unsubsidised Index Insurance Programme in Ethiopia. Issue 2 (1st February 2020) - Vasilaky, Kathryn; Diro, Rahel; Norton, Michael; McCarney, Geoff; Osgood, Daniel
Abstract: There is increasing concern that voluntary index insurance may fail to produce sustainable impacts at scale. Despite this concern, most research is focused on experimental or highly subsidised projects – little is known about farmer demand for market priced, commercially focused index insurance. We estimate the impact of attending a randomly administered education game for index insurance on the likelihood of purchase in the context of an unsubsidised, non-loan-linked commercial insurance programme in Ethiopia. This programme has already scaled to the tens of thousands via labour-based liquidity programmes and cash only sales. We find that the likelihood of purchasing unsubsidised insurance in commercial sales rose by an average of 10 per cent across villages, and that the average amount of insurance purchased increased by 33 per cent. These results demonstrate a possibility for financial education to increase demand, particularly among the subset of farmers who are not eligible for liquidity programmes.